DEPENDENSI DALAM MODEL RESIKO INDIVIDUAL UNTUK ASURANSI JIWA KELOMPOK - Pramesti, Getut; Kartiko, Sri Haryatmi (Journal of Mathematics and Mathematics Education, 2011)
ABSTRACT: TheÂ  riskÂ  dependenceÂ  ofÂ  anÂ  insuranceÂ  portfolioÂ  inÂ  aÂ  groupÂ  lifeÂ  insuranceÂ  canÂ  beÂ  describedÂ  asÂ  the individual risk model. It is used in modeling the claim distribution of insurance contracts over a fixed periodÂ  ofÂ  time.Â  TheÂ  distributionÂ  computationÂ  isÂ  conductedÂ  withÂ  directÂ  calculationÂ  throughtÂ  n convolution of individual claim distribution. We discuss the impact of the risk dependence on the net value of the stopâloss premium. A third risk factor in the dependence risk model is also introduced.Key words : The risk dependence, group life insurance, individual risk model, claim, the net value of the stop-loss premium.